Maladaptive emotional regulation in patients diagnosed with psychogenic non-epileptic seizures (PNES) compared with healthy volunteers - Krámská, Lenka; Hrešková, Lucia; Vojtěch, Zdeněk; Krámský, David; Myers, Lorna (Seizure, 2020)
PURPOSE: The term PNES refers to a conversion disorder that mimics epileptic seizures but has a psychological etiology. Recent studies report that in patients with PNES, there is reduced understanding of emotions, impulse control difficulties, and limited access to emotional regulation strategies. The aim of this study was to compare patients diagnosed with PNES with healthy volunteers on the presence of maladaptive emotional regulation. METHOD: Patients (N = 64 F:M 52:12; mean age 35.5 years; duration ≥ 2 years) were assessed while inpatients at the Epilepsy Center, Na Homolce Hospital, Prague. PNES diagnosis was based on normal EEG findings, habitual seizure capture, suggestive seizure provocation, neuropsychological assessment and patients´ history. The clinical sample was compared with healthy volunteers (N = 64 F:M 52:12; mean age 35.8 years). The presence of maladaptive emotional regulation was assessed through the Czech research version of the ASQ and DERS. RESULTS: Compared with a healthy sample, patients with PNES had greater emotion regulation impairments across nearly all dimensions of the DERS - Nonacceptance = 17.0 (M = 14.5), p = 0.006, Goals = 16.0 (M = 11.5), p < 0.001, Impulse control = 13.8 (M = 11.5), p = 0.005, Awareness = 16.4 (M = 15.3), p = 0.183, Strategies = 17.9 (M = 13.0), p < 0.001, Clarity = 11.8 (M = 9.5), p < 0.001 and the total score of the DERS = 92.9 (M = 75.3), p < 0.001. Similar results were found in ASQ questionnaire scales - Concealing = 24.5 (M = 21.0), p = 0.002, and Adjusting = 20.9 (M = 22.8), p = 0.076 but not on the Tolerating Scale = 14.5 (M = 14.7), p = 0.873. CONCLUSION: Our results highlight that maladaptive emotional regulation is a key psychological mechanism in PNES. Emotional dysregulation may represent an important target when designing psychoeducational and psychotherapeutic approaches for patients with PNES.
Keywords: záchvaty; Adult; Male; Emotional regulation; Seizures; lidé; Humans; adaptace psychologická; Conversion Disorder; Emotional Regulation; DERS; mužské pohlaví; emoční regulace; dospělí; konverzní poruchy; Adaptation, Psychological; Psychogenic non-epileptic seizures; ASQ; ženské pohlaví; Female